2018
DOI: 10.3390/app8081394
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Active Cancellation of Engine Order Noise in a Passenger Car

Abstract: This paper presents a novel active noise cancellation (ANC) method to reduce the engine noise inside the cabin of a car. During the last three decades, many methods have been developed for the active control of a quasi-stationary narrowband sinusoidal signal. However, since the interior noise signal is non-stationary with a fast frequency variation when the car accelerates rapidly, these methods cannot stably reduce the interior noise. The proposed method can reduce the interior noise stably even if the speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…However, it can lead to performance degradation due to the low data rates and delays [3]. In powertrain noise control, the fast convergence speed of the controller is critical because the engine speed changes rapidly, such as under full-load conditions [14]- [16]. Therefore, many adaptive filters with variable step size have been proposed [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it can lead to performance degradation due to the low data rates and delays [3]. In powertrain noise control, the fast convergence speed of the controller is critical because the engine speed changes rapidly, such as under full-load conditions [14]- [16]. Therefore, many adaptive filters with variable step size have been proposed [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used ANC techniques in the past successfully in various applications like reducing car engine noise. 6,7 Shi et al 8 observed that ANC was ideal for reducing low-frequency noise and was an incomparable addition to passive noise control. Narula et al 9 demonstrated ANC using Simulink and data acquisition toolbox; adaptive filters were used in real-time environment.…”
Section: Introductionmentioning
confidence: 99%
“…The undesired noise is reduced by emitting a sound signal with the same amplitude and opposite phase by means of an electroacoustic actuator [3]. Several ANC solutions have been tested in many industrial and automotive applications, e.g., portable generators [4], automotive [5,6] and locomotive [7] mufflers, car [8], aircraft [9] and yacht [10] cabins, ventilation ducts [11], power transformers [12], sound-proof windows [13], up to the well-known active headsets.…”
Section: Introductionmentioning
confidence: 99%